2021
DOI: 10.1186/s13014-020-01735-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and the gut microbiome: facts and fiction

Abstract: An ever-growing body of evidence has linked the gut microbiome with both the effectiveness and the toxicity of cancer therapies. Radiotherapy is an effective way to treat tumors, although large variations exist among patients in tumor radio-responsiveness and in the incidence and severity of radiotherapy-induced side effects. Relatively little is known about whether and how the microbiome regulates the response to radiotherapy. Gut microbiota may be an important player in modulating “hot” versus “cold” tumor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 118 publications
0
101
0
Order By: Relevance
“…Yi et al [ 86 ] identified potential microbial biomarkers for predicting the response to nCCRT in locally advanced rectal cancer: butyrate-producing bacteria, including Roseburia , Dorea , and Anaerostipes were overrepresented in responders, whereas Coriobacteriaceae and Fusobacterium were markedly higher in non-responders. Although gut dysbiosis could be a relevant biomarker to predict radiotherapy-induced mucositis [ 87 , 88 ], the direct impact on the patients’ response to radiotherapy has not yet been investigated yet. Recently Guo et al described in mice that radiation survivors could be identified by specific bacterial and metabolite profiles (Lachnosspiraceae and Enterococcaceae increases and downstream metabolites such as propionate and tryptophan pathways) [ 89 ].…”
Section: Gut Microbiota Biomarkers Predicting Prognosis And/or Treatment Responsementioning
confidence: 99%
“…Yi et al [ 86 ] identified potential microbial biomarkers for predicting the response to nCCRT in locally advanced rectal cancer: butyrate-producing bacteria, including Roseburia , Dorea , and Anaerostipes were overrepresented in responders, whereas Coriobacteriaceae and Fusobacterium were markedly higher in non-responders. Although gut dysbiosis could be a relevant biomarker to predict radiotherapy-induced mucositis [ 87 , 88 ], the direct impact on the patients’ response to radiotherapy has not yet been investigated yet. Recently Guo et al described in mice that radiation survivors could be identified by specific bacterial and metabolite profiles (Lachnosspiraceae and Enterococcaceae increases and downstream metabolites such as propionate and tryptophan pathways) [ 89 ].…”
Section: Gut Microbiota Biomarkers Predicting Prognosis And/or Treatment Responsementioning
confidence: 99%
“…Through this research, genus-and species-level identification and abundance across individuals and across their body regions (Table 1) have uncovered high inter-individual and intraindividual microbiota diversity that is impacted by co-evolutionary selection, age, diet, and geographic region (Mackie et al, 1999;Spor et al, 2011;Lozupone et al, 2012;Morgan and Huttenhower, 2012; or challenges (Bäckhed et al, 2005). Investigation of the virome, mycobiome, and archaea components of the microbiota broadly and particularly in response to radiation has been lacking (Rosenberg and Zilber-Rosenberg, 2013;Roy and Trinchieri, 2017;Liu et al, 2021). It is possible that broader insights into the impact of nonbacterial components of the GI microbiota might be obtained through non-targeted shotgun metagenomic sequencing techniques that would be capable of assessing radiation responses in the nonbacterial compartments of the GI microbiota (Campo et al, 2020;Kaźmierczak-Siedlecka et al, 2020;Turkington et al, 2021).…”
Section: History Of Microbiome Researchmentioning
confidence: 99%
“…As noted above, most studies of the effect of radiation on the GI microbiome have been conducted in the context of cancer radiotherapy, and recent reviews summarize the literature in that context (Liu et al, 2021;Tonneau et al, 2021). Indeed, therapeutic abdominopelvic radiation exposure frequently results in intestinal dysfunction and dysbiosis, with acute radiation enteritis complications observed in 50% or more of abdominally irradiated cancer patients (Touchefeu et al, 2014).…”
Section: Gut Microbiomementioning
confidence: 99%
“…As a novel approach to augment cancer therapy, they are thought to improve the diversity profile of the intestinal microbiota and reduce the extent of chronic inflammation and production of carcinogenic material in dysbiosis [ 2 , 95 , 96 ]. Prebiotics are non-digestible food constituents that selectively alter the growth of certain host-beneficial bacteria [ 97 ]. The combination of probiotics and prebiotics is called synbiotics.…”
Section: Effects Of Synbioticsmentioning
confidence: 99%